Major Barriers Assessment of Lean Construction Application in Construction Projects Delivery - Nwaki, Wiliam; Eze, Emmanuel; Awodele, Imoleayo (CSID Journal of Infrastructure Development, 2021)
The construction sector is facing challenges of meeting client’s value and end-user satisfaction, and this situation is worsened by customers’ dynamic demands for quality and speedy delivery without loss of value. Lean concept has been advocated to be a panacea to poor project performance, and it, however, has a high awareness level but with little implementation among construction organizations especially in developing countries including Nigeria. The purpose of this study is to assess the major barriers to lean construction application on construction project delivery, to suggest possible measures for overcoming them. A well-structured questionnaire was used to gather data from construction professionals in the south-south, Nigeria using electronic means and snowball sampling technique. Data gathered were analyzed using frequency, percentage and factor analysis. It was found that the major cluster of barriers to lean implementation are technology and knowledge barrier, leadership and management barrier, culture and complexity barrier, engagement and relationship barriers, financial barriers, and communication barriers. It was recommended that adequate management and leadership support is needed for entrenching lean construction techniques into the culture of operations of construction organisations.